The use of infrared thermography in endurance athletes: a systematic review - Romão, W.; Mello, D.; Neves, E. B.; Dias, T.; dos Santos, A. O. B.; Alkmim, R.; Vale, R. (Motricidade, 2021)
Infrared thermography (IRT) has become increasingly common in sports assessment and has grown a lot over the past few years. Our objective was to identify the assessment protocols and the skin temperature behavior of practitioners of endurance sports. A systematic review was carried out following the PRISMA recommendations between the 1st and the 31st of March 2020, at MEDLINE, LILACS, SCOPUS, SPORT Discus, CINAHL, Web of Science, Science Direct, Cochrane, and Scielo, using combinations with 11 descriptors for "Thermography" and 6 descriptors for "Endurance training". It was identified 24 different regions of interest (ROIs) evaluated region in endurance sports. The acclimatization time was respected in 75% of the selected studies, and the thermal images were acquired predominantly in three moments: before the test, immediately after the test, and 10 minutes after the test. It was observed that Tskin decreased in the initial moments and increased after exercise. It can be concluded that the ROIs used were mostly the specific muscle recruited in each modality, with emphasis on the muscle groups of the lower limbs, and after this initial decrease in temperature, the thermal response is mainly dependent on the duration and intensity of exercise.